Intentional multiple mating by females in a species where sneak fertilization circumvents female choice for parental males. Issue 2 (21st September 2018) - Stiver, Kelly A.; Kindsvater, Holly K.; Tamburello, Natascia; Heckman, Kellie L.; Klein, Joanne; Alonzo, Suzanne H.
Abstract : This paper describes how individual female ocellated wrasse Symphodus ocellatus distribute their spawning among males and nests in space and time. It is based on previously collected genetic data of larvae from ten different nests (used to reconstruct half and full‐sibling groupings both within and among nests on multiple days) and behavioural data of marked females across the reproductive season. Both the genetic analyses and behavioural observations confirm that female S. ocellatus intentionally engage in multiple mating, by repeatedly spawning at the same nest on different days and at several different nests (up to 12 spawning events over 3 weeks), leading to mixed paternity among her young. The main benefit of such high and intentional multiple mating is probably insurance against brood failure due to nest predation, desertion or poor paternal care by the male. These findings reveal that even in systems where females attempt to avoid male‐controlled mixed paternity, they may still engage in intentional multiple mating due to these potential benefits.